Protecting the Brain With Xenon Anesthesia for Neurosurgical Procedures. Issue 1 (January 2019) - Rylova, Anna; Maze, Mervyn
Abstract : Xenon possesses some, but not all, of the clinical features of an ideal anesthetic agent. Besides well-known advantages of rapid awakening, stable hemodynamics and lack of biotransformation, preclinical data lead to the expectation of xenon's advantageous use for settings of acute ongoing brain injury; a single randomized clinical trial using an imaging biomarker for assessing brain injury corroborated xenon's preclinical efficacy in protecting the brain from further injury. In this review, we discuss the mechanisms and hence the putative applications of xenon for brain protection in neurosurgery. Although the expense of this rare monoatomic gas will likely prevent its widespread penetration into routine clinical neurosurgical practice, we draw attention to the theoretical benefits of xenon anesthesia over other anesthetic regimens for awake craniotomy and for neurosurgery in older, high-risk, and sicker patients.